PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF GAME BERBASIS POWER POINT PADA MUATAN IPA KELAS IV SD NEGERI TANJUNGTIRTO II BERBAH - Ficsnata Mauri Setyaputri; Retno Utaminingsih (Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this study was to develop interactive learning media based on PowerPoint games for the fourth-grade science content at SD Negeri Tanjungtirto II Berbah. In addition, to determine the feasibility of the product produced and it has been validated by several experts to determine the responses and responses of students regarding the use of interactive learning media based on PowerPoint Games on science content carried out in class IV SD Negeri Tanjungtirto II Berbah. This research is a research and development research following the procedure of the Borg and Gall development model which is modified into seven steps. The data analysis technique used is qualitative and quantitative data analysis techniques. the results of material expert validation from all aspects obtained an average percentage of 96% including in the Very Good (BS) category. The results of media expert validation from all aspects obtained an average score percentage of 94% included in the Very Good (BS) category then the validation results from the fourth-grade homeroom teacher obtained an average percentage of 93.3% included in the Very Good (BS) category. The results of product trials with fourth-grade students obtained an average percentage score of 96.8% which was included in the Very Good (BS) category. Based on the data obtained, the interactive learning media based on PowerPoint Games is feasible to use.